2013
DOI: 10.1152/jn.00914.2012
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular benefits to task savings in motor adaptation

Abstract: Sarwary AM, Selen LP, Medendorp WP. Vestibular benefits to task savings in motor adaptation. J Neurophysiol 110: 1269 -1277, 2013. First published June 19, 2013 doi:10.1152/jn.00914.2012In everyday life, we seamlessly adapt our movements and consolidate them to multiple behavioral contexts. This natural flexibility seems to be contingent on the presence of movement-related sensorimotor cues and cannot be reproduced when static visual or haptic cues are given to signify different behavioral contexts. So far, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 35 publications
1
22
2
Order By: Relevance
“…Savings refers to the observation that when a subject adapts to perturbation (A), and then the perturbation is removed (i.e., washout), they exhibit faster readaptation to (A)(10). Remarkably, savings of (A) is present even when washout is followed by adaptation to (-A), a perturbation in the opposite direction (11, 12). Current error-dependent models of learning cannot account for these observations (13, 14), nor explain meta-learning, where prior exposure to a random perturbation produces savings (15, 16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Savings refers to the observation that when a subject adapts to perturbation (A), and then the perturbation is removed (i.e., washout), they exhibit faster readaptation to (A)(10). Remarkably, savings of (A) is present even when washout is followed by adaptation to (-A), a perturbation in the opposite direction (11, 12). Current error-dependent models of learning cannot account for these observations (13, 14), nor explain meta-learning, where prior exposure to a random perturbation produces savings (15, 16).…”
mentioning
confidence: 99%
“…Error-sensitivity modulation was specific to the experienced errors, suggesting that training produced a memory of errors. This idea accounted for a host of puzzling observations, including saturation of error-sensitivity (5, 6, 29), the phenomenon of meta-learning (16), examples of savings (1012), and reinforced repetition (15). …”
mentioning
confidence: 99%
“…Several studies have shown that the brain anticipates Coriolis torques on the limb that are generated during active torso rotation (Pigeon et al 2013;Sainburg et al 1999) and adapts reaches while on a rotating or translating platform (Lackner and Dizio 1994;Sarwary et al 2013). However, it is unclear if, and how, the brain anticipates biomechanical costs in deciding which hand to use when one is reaching for a target during passive whole body translations.…”
mentioning
confidence: 99%
“…Furthermore, the brain adapts its control policy to the Coriolis torques felt during reaches made in rotating environments (see Lackner and Dizio, 2005, for review). Similarly, we showed that human subjects adapt their control policy for reaching under passive lateral translation on a vestibular platform, inducing inertial forces on the arm (Sarwary et al, 2013).…”
Section: Learning and Recallmentioning
confidence: 60%
“…We tested this recently, asking subjects to reach while their body was passively translated laterally (Sarwary et al, 2013). We switched the coupling between the direction of a reaching movement (forwardbackward) and the direction of whole-body motion (leftward-rightward) every 160 trials (see Fig.…”
Section: Learning and Recallmentioning
confidence: 99%